KEMITRAAN STRATEGIS DALAM IMPLEMENTASI CSR DI KOTA MAKASSAR : PERAN AKTOR UTAMA - Nani Harlinda Nurdin; Imran Ismail; Nining Haslinda Zainal; Muhammad Ridha Suaib (Journal Publicuho, 2024)
This study explores the implementation of the Corporate Social Responsibility (CSR) program in Makassar City, focusing on the roles of government, private sector and society in supporting sustainable development. Through analysis of local regulations and active contributions from various parties, this research shows how the collaboration of these three actors can create a positive impact in overcoming social, economic and environmental challenges at the local level. These findings provide important insights for practitioners and researchers to understand the dynamics of CSR implementation in local government contexts, with implications for more effective and sustainable public policy.